Respostas
respondido por:
1
Oi,
2 - 3x = - 9 - 4
- 3x = - 9 - 4 - 2
- 3x = - 15 . ( - 1 )
3x = 15
x = 15/3
x = 5
Espero ter ajudado e bons estudos !
2 - 3x = - 9 - 4
- 3x = - 9 - 4 - 2
- 3x = - 15 . ( - 1 )
3x = 15
x = 15/3
x = 5
Espero ter ajudado e bons estudos !
Liaromancini:
De nada !
respondido por:
1
2-3x=-9-4
-3x=-9-4-2
-3x=-15
x=-15-/-3
x=5
porque -/- é igual a + por isso e igual 5
-3x=-9-4-2
-3x=-15
x=-15-/-3
x=5
porque -/- é igual a + por isso e igual 5
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás